Analisis Penggunaan Microsoft Excel sebagai Sistem Informasi Akuntansi pada UMKM di Jakarta - Salman Alfarisi Muharram; Deni Darmawati (Ikatan Da'i Indonesia, 2026)
This study explores financial recording issues faced by small businesses in Jakarta whose bookkeeping practices remain basic and do not yet provide information sufficient for decision-making. These conditions highlight the need to analyze how Excel is actually utilized as a structured financial recording tool. The purpose of this study is to evaluate how four micro businesses use Excel, covering data entry, processing, and output, as well as the benefits perceived by owners. A qualitative descriptive method was applied through interviews, observations, and document analysis. The novelty of this study lies in comparing four different business sectors, allowing variations in Excel usage to be observed based on operational characteristics. The findings show that Excel improves accuracy, efficiency, and understanding of business performance, although its use is still limited by user skills and the absence of standardized formats. The study concludes that Excel is feasible as a basic solution. Its implications encourage targeted training, while future research may test standardized templates.